PENGARUH FASILITAS SEKOLAH TERHADAP MOTIVASI SISWA DALAM PROSES BELAJAR DI “SMPN 1 JIWAN” KAB. MADIUN TAHUN PELAJARAN 2011/2012 - Wiwin Sumaryati (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2013)
This study aims to determine whether or not the effect of school facilities on student motivation in SMP N 1 Jiwan Academic Year 2011/2012. Determination of the sample in this study using a random sampling of the number of 48 students comprising the class 7A and 7B. The data collection method kueisioner. In analyzing the data using a simple linear regression, and to test whether the instrument is valid using the t test. The results indicate that school facilities have an influence on students’ motivation in the learning process in SMP N 1 Jiwan Year 2011/2012. It is obtained from the calculation of the t test showed that thitung (2.5)> ttabel of 1.684 which was exhibited significantly at the level of 0.05 (5%), Ho is rejected which means that there was an effect of school facilities on student motivation in the learning process. Judging from the results of calculations using the t test derived regression equation Y = 26.717 + 0.346 X, which means that if the school facility experienced a 1% increase the motivation of students in the learning process has increased by 0.346%. It can be concluded that there was an effect of school facilities on student motivation in the learning process in SMP N 1 Jiwan Madison County Academic Year 2011/2012.